2021
DOI: 10.6007/ijarbss/v11-i9/10856
|View full text |Cite
|
Sign up to set email alerts
|

Understanding English as a Foreign Language (EFL) Teachers’ Acceptance to Teach Online During Covid-19: A Chinese Case

Abstract: To contain the spread of Covid-19, the Ministry of Education of China postponed the opening of schools for face-to-face lessons and launched an initiative of "postponement of school without suspension of learning". Therefore, nearly all educational institutions across China moved from traditional teaching practices to online teaching in the Spring semester of 2020. English language teachers in Chinese universities had to move their traditional physical instruction to online. The paper is designed to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…College teachers of English as a foreign language (EFL) in China are being encouraged by national policies to make use of advanced technology so as to create authentic, language-rich learning environments in their teaching practice [6]. However, insufficient technical proficiency, as well as the lack of confidence in technology use, has negatively affected EFL teachers' efforts to embrace technology [7]. Previous literature has shown that Chinese EFL teachers were not enthusiastic about using technology in their classrooms [8].…”
Section: Introductionmentioning
confidence: 99%
“…College teachers of English as a foreign language (EFL) in China are being encouraged by national policies to make use of advanced technology so as to create authentic, language-rich learning environments in their teaching practice [6]. However, insufficient technical proficiency, as well as the lack of confidence in technology use, has negatively affected EFL teachers' efforts to embrace technology [7]. Previous literature has shown that Chinese EFL teachers were not enthusiastic about using technology in their classrooms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their inadequate preparation for the emerging phenomenon of remote teaching, English language teachers faced new challenges in developing their online instructional skills in parallel with standard online courses [ 5 ]. Consequently, some English language teachers showed negative attitudes toward, or even refused to conduct, online teaching, which would definitely deteriorate online education quality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%